2013
DOI: 10.3233/fi-2013-873
|View full text |Cite
|
Sign up to set email alerts
|

Chameleon Hash Functions and One-Time Signature Schemes from Inner Automorphism Groups

Abstract: In this paper, we build a family of chameleon hash functions and strongly unforgeable one-time signature schemes based on the intractability assumption of the discrete logarithm problem (DLP) over inner automorphism groups. Since the DLP assumption over inner automorphism groups does not admit sub-exponential attacks, thus the sizes of the working parameters used in our constructions are shorten significantly. This leads to remarkable gains for our proposals both in running time and in storage space. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Later, Chen et al suggested a DLP-based key-exposure-free chameleon hash and signature system that did not need the gap Diffie-Hellman groups [7]. Pan et al proposed a family of chameleon hash functions and strongly unforgeable one-time signature schemes based on DLP over inner automorphism groups [8].…”
Section: Related Workmentioning
confidence: 99%
“…Later, Chen et al suggested a DLP-based key-exposure-free chameleon hash and signature system that did not need the gap Diffie-Hellman groups [7]. Pan et al proposed a family of chameleon hash functions and strongly unforgeable one-time signature schemes based on DLP over inner automorphism groups [8].…”
Section: Related Workmentioning
confidence: 99%